Cultural Appropriation and Ritual Negotiation: Salafi and HTI Strategies in Minangkabau, Indonesia - Zakirman, Zakirman; Mahmudi, Elva; Bary, Shafwatul (Journal of Contemporary Rituals and Traditions, 2025)
Purpose: This study explores the cultural and spiritual appropriation strategies employed by transnational Islamic movements, specifically Salafi and Hizbut Tahrir Indonesia (HTI), in their expansion and dissemination of religious teachings in West Sumatra, Indonesia. The research focuses on how these groups utilize local cultural identities, values, and symbols to embed themselves within the social and religious landscape of the region. Methodology: Using a qualitative, descriptive-analytical approach, data were collected through in-depth interviews, content analysis, and literature review from books, websites, and academic studies. West Sumatra was chosen as the case study due to its historical openness to Islamic teachings and its recent ranking as one of the least religiously moderate provinces in Indonesia. Findings: The findings revealed that transnational Islamic groups successfully appropriate local cultural elements to minimize resistance and enhance acceptance, mirroring the historical spread of Islam in the region. These groups utilize various vehicles, including educational institutions, traditional and digital media, and religious gatherings, to advance their ideological missions. Implications: This study expands the application of cultural appropriation theory by examining how transnational religious ideologies adapt symbolically to local cultures. The findings are also practically relevant for policymakers and communities in formulating religious moderation strategies and detecting ideological infiltration through cultural channels. Originality and Value: Its originality lies in its regional focus and its interdisciplinary analysis of religious expansion through the lens of cultural adaptation, providing a nuanced understanding of contemporary Islamic movements in Indonesia.